Meningkatkan Hasil Belajar IPAS Siswa SD dengan Model PBL berbantu Media Policermat - Naning Zuaria Kusuma Mastuti; Siti Masfuah; Eka Zuliana (Universitas Ngudi Waluyo, 2025)
Abstract This study aims to improve the science learning outcomes of fifth-grade students at SDN 4 Mulyolobo Jepara, who in the pre-cycle only achieved 5.56% mastery due to teacher-centered learning and minimal media innovation. The solution used is Problem-Based Learning (PBL) assisted by Policermat (Monopoly Cerdas Cermat) media to encourage active involvement, critical thinking, collaboration, and create an interactive and enjoyable learning atmosphere. This Classroom Action Research involved 18 students and lasted for two cycles, each with two meetings. Data were obtained through tests, observations, interviews, and documentation, then analyzed quantitatively and qualitatively. The results showed an increase in learning mastery from 5.60% in the pre-cycle to 38.90% in Cycle I, and 83.30% in Cycle II (a total increase of 77.7%). In Cycle II, students’ IPAS process skills also demonstrated significant improvement, with achievements as follows: observing 86.83%, questioning and answering 83.34%, planning and conducting investigations 77.78%, associating 84.00%, and communicating 82.64%. Based on IPAS assessments, students’ learning outcomes also improved, with scores of C1 (Remembering) 79.40%, C2 (Understanding) 73.98%, C3 (Applying) 70.58%, C4 (Analyzing) 66.95%, C5 (Evaluating) 62.45%, and C6 (Creating) 61.95%. Abstrak Penelitian ini bertujuan meningkatkan hasil belajar IPAS siswa kelas V SDN 4 Mulyolobo Jepara yang pada pra-siklus hanya mencapai ketuntasan 5,56% akibat pembelajaran berpusat pada guru dan minim inovasi media. Solusi yang digunakan adalah Problem-Based Learning (PBL) berbantu media Policermat (Monopoli Cerdas Cermat) untuk mendorong keterlibatan aktif, berpikir kritis, kolaborasi, serta menciptakan suasana belajar yang interaktif dan menyenangkan. Penelitian Tindakan Kelas ini melibatkan 18 siswa dan berlangsung selama dua siklus, masing-masing dua kali pertemuan. Data diperoleh melalui tes, observasi, wawancara, dan dokumentasi, lalu dianalisis secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan peningkatan ketuntasan belajar dari 5,60% pada pra-siklus menjadi 38,90% pada siklus I, dan 83,30% pada siklus II (kenaikan total 77,7%). Pada siklus II menunjukkan keterampilan proses IPAS siswa sudah berkembang baik dengan capaian mengamati 86,83%, menanya dan menjawab 83,34%, merencanakan dan melakukan penyelidikan 77,78%, mengasosiasikan 84,00%, dan mengomunikasikan 82,64%. Berdasarkan penilaian IPAS, hasil belajar siswa juga meningkat dengan capaian C1 79,40%, C2 73,98%, C3 70,58%, C4 66,95%, C5 62,45%, dan C6 61,95%.